A dual Lagrange method for contact problems with regularized frictional contact conditions: Modelling micro slip - Sitzmann, Saskia; Willner, Kai; Wohlmuth, B. I. (Computer Methods in Applied Mechanics and Engineering, 2015)
This paper presents an algorithm for solving quasi-static, non-linear elasticity contact problems with friction in the context of rough surfaces. Here, we want to model the transition from sticking to slipping also called micro slip in a physically correct way in order to reproduce measured frictional damping. The popular dual Mortar method is used to enforce the contact constraints in a variationally consistent way without increasing the algebraic system size. The algorithm is deduced from a perturbed Lagrange formulation and combined with a serial-parallel Iwan model. This leads to a regularized saddle point problem, for which a non-linear complementary function and thus a semi-smooth Newton method can be derived. Numerical examples demonstrate the applicability to industrial problems and show good agreement to experimentally obtained results.
Keywords: Constitutive contact equations; Contact with friction; Dual Mortar methods; Iwan model; Micro slip; Rough surfaces